Amyotrophic Lateral Sclerosis: First Case Report in Department of Neurosurgery, Faculty of Medicine, Universitas Padjadjaran, Bandung - Ahmad Faried; Priandana Adya Eka Saputra; Alief Dhuha; Muhammad Zafrullah Arifin (International Journal of Integrated Health Sciences, 2019)
Objective: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that is incurable and results in paralysis of the muscles. Electromyography (EMG) is used to diagnosis amyotrophic lateral sclerosis. Although recently there is no cure for ALS, knowledge has increased significantly in the past several years and is helping those who are newly diagnosed.Methods: This study reported for the first time in Department of Neurosurgery, Faculty of Medicine, Universitas Padjadjaran-Dr. Hasan Sadikin General Hospital, Bandung a 58-year old man who was presented in the institution with a history of weakness of both lower extremities for four months preceded by weakness of both upper extremities since the previous month. There was no history of any medical illness or any chronic medication. The patient then underwent EMG studies, followed by muscle biopsy.Result: Electromyography and histopathological results confirmed a diagnosis of ALS.Conclusion: This case was so exceptional, since ALS occurrence in Neurosurgery Centre is extremely rare, and the diagnosis can only be established through EMG and histopathological of muscle biopsy studies.Keywords: The fist reported of ALS in Neurosurgery Bandung, electromyography studies